STRATEGI KAMPANYE DIGITAL ANTI HOAKS PROGRAM TULAR NALAR-MAFINDO DI KOTA BATAM - Marisa Triargarini; Riswandi Riswandi (LPPM Universitas Putera Batam, 2025)
Hoaxes have become a serious issue in the digital era, especially among new internet users who often lack digital literacy. This study aims to analyze the anti-hoax digital campaign strategy implemented by the Tular Nalar-MAFINDO Program in Batam City. The campaign responds to the increasing spread of false information, particularly among the elderly and students. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal that the campaign strategy was built on clear audience segmentation, multi-stakeholder collaboration, and media selection tailored to target characteristics. The program consists of two main segments: Akademi Digital Lansia (ADL) and Sekolah Kebangsaan (SK), each applying specific communication approaches. Elderly participants responded better to conventional media such as booklets and leaflets, while students were more effectively reached through digital platforms like Instagram and WhatsApp. Evaluation using pre-tests, post-tests, and behavioral observation showed increased awareness and ability to identify hoaxes. The study concludes that a community-based, participatory, and digitally integrated approach can strengthen public resilience against disinformation. The results are expected to serve as a reference for future digital literacy programs in Indonesia